Forest fire / Abd Malek Samsudin - Samsudin, Abd Malek (2009)
Forest fire is a new phenomenon in Malaysia. It is separated into three parts. Three parts are surface fire, crown fire, and ground fire. Forest fire can happen because of several factors. Among them are bad weather, forest utilization, land preparations, land occupancy, incendiary and natural causes. Forest fire has effected the environment and human for a long time or in short time period such as air pollution, disease infection, and increase world temperature and other. Steps that were taken by certain party such as give awareness to people about the danger of forest fire in our life. Using the high technology equipment in detecting forest fire help to decrease it and also by using the incendiary. In that way total of fire forest can be decrease and problem can be settled.